Youngia jianningensis (Asteraceae), a new species from China: evidence from morphological and DNA analyses - Chen, Yong-Bin; Zhou, Cheng-Yuan; Gao, Yuan-Long; Ma, Liang; Lin, Feng; Chen, Shi-Pin (Phytotaxa, 2025)
Youngia jianningensis, a new species from Jianning County, Fujian Province, China, is described and illustrated based on morphology and DNA analysis. Morphological comparisons indicated that this species is similar to Y. jiulongshanensis and Y. heterophylla, but differs by its slender and soft stems, different leaf shapes, number of florets per capitula and number of inner phyllaries. Phylogenetic analyses based on nuclear ribosomal ITS and three plastid marker sequences (atpB-rbcL, psbA-trnH and trnL-trnF) support that the new species is closely related to Y. jiulongshanensis.